Constraining multi-stage exposure-burial scenarios for boulders preserved beneath cold-based glacial ice in Thule, northwest Greenland - Corbett,LB; Bierman,PR; Rood,DH (Earth and Planetary Science Letters, 2016)
Boulders and landscapes preserved beneath cold-based, nonerosiveglacial ice violate assumptions associated with simple cosmogenicexposure dating. In such a setting, simple single isotope exposure agesover estimate the latest period of surface exposure; hence, alternateapproaches are required to constrain the multi-stage exposure/burialhistories of such samples. Here, we report 28 paired analyses of 10Be and26Al in boulder samples from Thule, northwest Greenland. We use numericalmodels of exposure and burial as well as Monte Carlo simulations toconstrain glacial chronology and infer process in this Arctic regiondominated by cold-based ice. We investigate three specific cases that canarise with paired nuclide data: (1) exposure ages that are coeval withdeglaciation and 26Al/10Be ratios consistent with constant exposure; (2)exposure ages that pre-date deglaciation and 26Al/10Be ratios consistentwith burial following initial exposure; and (3) exposure ages that predatedeglaciation and 26Al/10Be ratios consistent with constant exposure.Most glacially-transported boulders in Thule have complex histories; somewere exposed for tens of thousands of years and buried for at leasthundreds of thousands of years, while others underwent only limitedburial. These boulders were recycled through different generations oftill over multiple glacial/interglacial cycles, likely experiencingpartial or complete shielding during interglacial periods due to rotationor shallow burial by sediments. Our work demonstrates that the landscapein Thule, like many high-latitude landscapes, was shaped over long timedurations and multiple glacial and interglacial periods throughout theQuaternary.